2021
DOI: 10.1007/s00167-021-06450-w
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic umbilical cord blood-derived mesenchymal stromal cell implantation was superior to bone marrow aspirate concentrate augmentation for cartilage regeneration despite similar clinical outcomes

Abstract: PurposeThe aim of this study was to compare clinical and second‐look arthroscopic outcomes between bone marrow aspirate concentrate (BMAC) augmentation and human umbilical cord blood‐derived mesenchymal stromal cell (hUCB‐MSC) implantation in high tibial osteotomy (HTO) for medial compartmental knee osteoarthritis and identify the relationship between articular cartilage regeneration and HTO outcomes. MethodsA total of 176 patients who underwent HTO combined with a BMAC or hUCB‐MSC procedure for medial compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 56 publications
2
67
1
Order By: Relevance
“…The effect was superior to HA [35]. For patients receiving high tibial osteotomy, the intraarticular addition of bone marrow aspirate concentrate or human umbilical cord blood-derived MSCs provided similar, outcomes in terms of pain relief, functional scores, and quality of life at a mean follow-up of 33 months [36].…”
Section: Intraarticular Injectionsmentioning
confidence: 86%
“…The effect was superior to HA [35]. For patients receiving high tibial osteotomy, the intraarticular addition of bone marrow aspirate concentrate or human umbilical cord blood-derived MSCs provided similar, outcomes in terms of pain relief, functional scores, and quality of life at a mean follow-up of 33 months [36].…”
Section: Intraarticular Injectionsmentioning
confidence: 86%
“…Such heterogeneity exists in studies using various animal models of OA in preclinical studies ( Cope et al, 2019 ; Wang et al, 2022 ), as well as clinical trials. Despite these limitations, several clinical trials have recently reported on the efficacy of exogenous MSCs to regenerate cartilage in OA ( Table 1 ) ( Emadedin et al, 2018 ; Kuah et al, 2018 ; Freitag et al, 2019 ; Khalifeh Soltani et al, 2019 ; Lee et al, 2019 ; Lu et al, 2019 ; Matas et al, 2019 ; Shapiro et al, 2019 ; Anz et al, 2020 ; Yang et al, 2022 ). Across these trials, methodologic heterogeneity has hindered a standardized approach to MSC-based therapies, including the use of host source (allogeneic vs. autologous), tissue source (bone marrow, adipose, umbilical cord, and placenta), injectate (tissue concentrates vs. isolated MSCs), whether they were expanded in vitro prior to injection, the dosage used, and the delivery method (e.g., image-guided or not).…”
Section: Cell-based Therapies For Osteoarthritismentioning
confidence: 99%
“…Similarly, the tissue of origin of exogenous MSCs transplanted into the site of cartilage injury will also be a primary factor toward successful cartilage regeneration. Interestingly, while studies have compared stem cell chondrogenic capacity from different niches in vitro ( Mochizuki et al, 2006 ; Koga et al, 2008 ), and studies have compared stem cells to implanted chondrocytes ( Nejadnik et al, 2010 ) and bone marrow concentrate ( Yang et al, 2022 ) in vivo , we are not aware of any in vivo studies directly comparing chondrogenic repair capacities of different stem cell populations derived from different tissue sources. To date, clinical trials evaluating MSCs have shown some evidence of reducing OA-associated pain and can produce cartilage in vitro , but there is little evidence that current MSC treatment regenerates damaged cartilage in vivo .…”
Section: Future Avenues For Stem Cell Therapy For Cartilage Regenerationmentioning
confidence: 99%
“…The patients were followed for a minimum of one year, and at the final follow-up, the median IKDC subjective score, the WOMAC score, the KSS pain and function scores, and the HSS improved significantly. Yang et al [ 119 ] compared clinical and second-look arthroscopic outcomes between bone marrow aspirate concentrate (BMAC) augmentation and UC-MSCs transplantation in HTO for medial compartmental knee OA. At a mean follow-up of 33 months, clinical outcomes including IKDC, KOOS, SF-36, and Tegner activity scores were significantly improved in both groups, but there were no differences between the two groups.…”
Section: Clinical Perspectivementioning
confidence: 99%